2007
DOI: 10.1159/000101855
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factors C and D Represent Novel Prognostic Markers in Colorectal Carcinoma Using Quantitative Image Analysis

Abstract: Background/Aims: Vascular endothelial growth factor C (VEGF-C) and vascular endothelial growth factor D (VEGF-D) are potent lymphangiogenic and angiogenetic mediators in many kinds of tumors. However, the exact impacts of VEGF-C and VEGF-D on the prognosis of colorectal cancer (CRC) remain elusive. The aims of this study were to demonstrate the expression of VEGF-C and VEGF-D and to correlate their expression levels with clinicopathological factors and long-term survival in patients with CRC. Patients and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 51 publications
3
20
1
2
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13] In CRC tissues, the expression level of VEGF-C has been shown to be significantly correlated with lymph node metastasis. [14][15][16][17][18] In the present study, we found that elevated expression of VEGF-C significantly correlated with LMVD and lymph node metastasis. Lymphatic vessel invasion is thought to precede or occur coincidently with lymph node metastasis.…”
Section: Discussionsupporting
confidence: 51%
“…[5][6][7][8][9][10][11][12][13] In CRC tissues, the expression level of VEGF-C has been shown to be significantly correlated with lymph node metastasis. [14][15][16][17][18] In the present study, we found that elevated expression of VEGF-C significantly correlated with LMVD and lymph node metastasis. Lymphatic vessel invasion is thought to precede or occur coincidently with lymph node metastasis.…”
Section: Discussionsupporting
confidence: 51%
“…Metastasis is one of the major causes of cancer-related mortality (31)(32)(33)(34)(35). At present, there is an intense effort to identify potential therapeutic agents that inhibit metastasis (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] For example, the lack of specificity of TKIs may result in adverse effects, as well as the desired blockade of VEGF-A-mediated activities. In addition, an antibody specific for VEGF-A may not have maximal efficacy if VEGF-C and -D are overexpressed in tumor specimens 8 since VEGF-C and VEGF-D are ligands for VEGFR-2 and VEGFR-3. 9,10 Herein is described the preclinical development of CT-322, the first example of an Adnectin TM to enter clinical trials.…”
Section: Suppl Material)mentioning
confidence: 99%